Serological testing of an equal-volume milk sample – a new method to estimate the seroprevalence of small ruminant lentivirus infection? - Adrian-Valentin Potârniche; Michał Czopowicz; Olga Szaluś-Jordanow; Agata Moroz-Fik; Marcin Mickiewicz; Kinga Biernacka; Lucjan Witkowski; Iwona Markowska-Daniel; Emilia Bagnicka; Constantin Cerbu; Diana Olah; Emilia Trif; et al. (BMC Veterinary Research, 2023)
Abstract Background In cattle attempts to evaluate within-herd prevalence of various infectious and parasitic diseases by bulk-tank milk (BTM) testing with ELISA have been made with moderate success. The fact that BTM is composed of variable and unknown volumes of milk from individual lactating animals weakens the relationship between numerical result of the ELISA and the within-herd prevalence. We carried out a laboratory experimental study to evaluate if a pooled milk sample created by mixing an equal volume of individual milk samples from seropositive and seronegative goats, henceforth referred to as an equal-volume milk sample (EVMS), would allow for accurate estimation of within-herd seroprevalence of caprine arthritis-encephalitis (CAE) using 3 different commercial ELISAs. By mixing randomly selected milk samples from seronegative and seropositive goats, 193 EVMS were created – 93 made of seronegative samples and 100 with the proportion of seropositive individual milk samples (EVMS%POS) ranging from 1 to 100%. EVMS%POS could be considered as a proxy for the within-herd seroprevalence. Then, OD of EVMS (ODEVMS) of the 193 EVMS was measured using 3 commercial ELISAs for CAE – 2 indirect and 1 competitive. Results The cut-off values of ODEVMS indicating SRLV infection were determined. The regression functions were developed to link ODEVMS with EVMS%POS. A significant monotonic relationship between ODEVMS measured with 2 commercial indirect ELISAs and EVMS%POS was identified. Two regression models developed on this basis described approximately 90% of variability and allowed to estimate EVMS%POS, when it was below 50%. High ODEVMS indicated EVMS%POS of > 50%. Conclusion Our study introduces the concept of serological testing of EVMS as a method of detecting SRLV-infected herds and estimating the proportion of strongly seropositive goats. Further field studies are warranted to assess practical benefits of EVMS serological testing.